Analysis of the Implementation of Permendikbudristek no. 63 of 2022 Concerning Managemet of School Operational Assistance Funds (BOS) at Madrasah Ibtidaiyah (MI) Sultan Hasanuddin Jakarta - Oktafiani, Annisa; Nasution, Hafifah; Muhammad Zairin, Gentiga (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
School Operational Assistance (BOS) is a government program which basically provides funding for non-personnel operating costs for educational units, targeting all schools. Regulation of the Minister of Education, Culture, Research and Technology (Permendikbudristek) no. 63 of 2022 concerning Technical Guidelines for Management of BOS Funds explains that procedures for using BOS funds consisting of planning, implementation, reporting and supervision must be based on the principles of flexibility, effectiveness, efficiency, accountability and transparency as accountability for good management of education costs to the government and public. This research aims to analyze the implementation of Permendikbudristek no. 63 of 2022 concerning the management of BOS funds at Madrasah Ibtidaiyah (MI) Sultan Hasanuddin Jakarta. This study used descriptive qualitative method. Principals, treasurers and teachers as research subjects. Data collection techniques include observation, interviews and documentation. The data analysis process is carried out by reducing the data, then the data is presented, and then conclusions are drawn. Meanwhile, the validity of the data uses triangulation techniques. The research results show that the management of BOS funds at MI Sultan Hasanuddin Jakarta is in accordance with regulations including management procedures consisting of planning, implementation, reporting and supervision. Then it has implemented the principles of flexibility, effectiveness, efficiency, accountability and transparency, but it is still not optimal. Because there is no role for the school committee. Then the accountability report for the use of funds is not yet complete, and the principle of transparency has not been implemented by publishing it to all parties.